The relationship of speed and changes of direction speed on agility among rugby union players / Muhammad Afiq 'Izzat Zulkifli - Zulkifli, Muhammad Afiq 'Izzat (Faculty of Sport Science and Recreation, 2017)
Rugby union is high-force contact based group activity that need players to have a different scope of physical properties. Players on the attacking side will advance with the ball by evading players on the defense, and players on defense will try to stop the movement of players on the offense who are trying to avoid them. Agility is an important component of many sports and may be defined as a rapid whole body movement with change of direction in response to a stimulus (Sheppard & Young; 2006). The correlation of 10m sprint on agility. r= 0.75 and p-value <0.001. As the result shows, the Pearson's correlation, r is 0.75.. Then, the p value or Sig. (2-tailed) is <0.001. Table 3 shows the correlation of30m sprint on agility. r= 0.47 and p-value p>0.005. As the result shows, the Pearson's correlation, r is 0.47. The value is in the middle value in correlation coefficient. So it is in moderate correlation coefficient which is in range of (0.30-0.49). Table 4 shows the correlation of changes of direction speed on agility. r= 0.60 and p value <0.001. As the result shows, the Pearson's correlation, r is 0.60. Then, the p value or Sig. (2-tailed) is <0.001. In conclusion study found that there is significance relation relationship of speed and changes of direction speed on agility among rugby union players. This is because, speed and changes of direction speed combines produces agility. The execution of agility is depending on the execution of speed and also changes of direction speed.